Pengaruh Board Size, Leverage, dan Kualitas Audit terhadap Nilai Perusahaan - Herni Kurniati (STIE Indonesia Banking School, 2016)
This study aimed to examine the effect of board size, leverage, and audit quality of the company's value in the property and real estate company listed on the Indonesia Stock Exchange (BEI) in 2010-2014. The variables tested in this study consisted of board size, leverage, and audit quality indicators auditor competence and independence of auditors and the company's value. The object of this research is company property and real estate that is growing lately, which is listed on the Indonesia Stock Exchange period 2010-2014. This study used linear regression to examine whether there is a significant positive effect between the independent variable on the dependent variable, where the independent variables tested were board size, leverage, and audit quality, while the dependent variable is the value of the company. Data using multiple regression analysis to answer the research hypothesis with the Eviews 6. The results of this study are (1) board size positive effect on the value of the company, (2) Leverage does not affect the value of the company. (3) The audit quality as measured by the competence of auditors has no effect on the value of the company, while the audit quality as measured by the auditor's independence positive significant effect on firm value. The implications of this study is to provide investment options to investors in using the money to invest (not only invest in companies manufacturing and banking).